Analisis Dan Evaluasi Protokol Keamanan Jaringan Nirkabel Wi-Fi Protected Access 3 dengan Metode Penetration Testing - Faishol, Dimas Erisma; Cahyanto, Triawan Adi; Rahman, Miftahur (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Information and communication technology is something that is integral to life in today's era. One of them is a wireless network. This research uses the Penetration Testing method to analyze the wireless technology security system that we often use every day. Analyzing wireless network security is carried out using the Penetration Testing method by carrying out attacks on a simulated network, the operating system used to carry out testing is Kali Linux. The results of this research show that network security using the WPA3 protocol is still vulnerable to gaps that can be exploited. This hacking test is only for educational purposes, it is not permitted to commit crimes such as stealing personal data of network users. By knowing this security gap, it will be an evaluation to provide better security